Age-related decline in the expression of GDF9 and BMP15 genes in follicle fluid and granulosa cells derived from poor ovarian responders - Yan Gong; Jesse Li-Ling; Dongsheng Xiong; Jiajing Wei; Taiqing Zhong; Hao Tan (BMC, 2021)
Abstract Background Growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) genes play important roles in folliculogenesis. Altered expression of the two have been found among patients with poor ovarian response (POR). In this prospective cohort study, we have determined the expression of the GDF9 and BMP15 genes in follicle fluid (FF) and granulosa cells (GCs) derived from poor ovarian responders grouped by age, and explored its correlation with the outcome of in vitro fertilization and embryo transfer (IVF-ET) treatment. Methods A total of 196 patients with POR were enrolled from a tertiary teaching hospital. The patients were diagnosed by the Bologna criteria and sub-divided into group A (< 35 year old), group B (35-40 year old), and group C (> 40 year old). A GnRH antagonist protocol was conducted for all patients, and FF and GCs were collected after oocyte retrieval. Expression of the GDF9 and BMP15 genes in the FF and GCs was determined with enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. Results Compared with group C, groups A and B had significantly more two pronuclei (2PN) oocytes and transplantable embryos, in addition with higher rates of implantation and clinical pregnancy (P <  0.05). The expression level of GDF9 and BMP15 genes in the FF and GCs differed significantly among the three groups (P <  0.05), showing a trend of decline along with age. The ratio of GDF9/BMP15 mRNA levels were similar among the three groups (P > 0.05). The relative levels of GDF9 and BMP15 proteins in GCs have correlated with the relative mRNA levels in GCs and protein concentrations in FF (P <  0.05). Conclusions For poor ovarian responders, in particular those over 40, the expression of GDF9 and BMP15 is declined along with increased age and in accompany with poorer oocyte quality and IVF outcome, whilst the ratio of GDF9/BMP15 mRNA levels remained relatively constant. Trial registration Chinese Clinical Trial Registry Center ( ChiCTR1800016107 ). Registered on 11 May 2018.